Keanekaragaman Capung di Kecamatan Kerkap Kabupaten Bengkulu Utara - Rukiah Lubis; Apriza Fitriani; Desilia Safitri (Jurusan Biologi Universitas Negeri Makassar, 2021)
This research aims to determine the diversity of dragonflies in Kerkap District, Bengkulu Utara regency. The location of this research in 5 villages located ini Kerkap District, Nort Bengkulu Regency. This study used a direct survey method to the research location that was conducted in february – march 2021. The sample was taken using purposive sampling method. Based on the researchnresults found 3 families, namely Lindeniidae (Ictinogomphus australis) two species of the Coenagrionidae family were found (ischnura ramburii and ischnura elegans). while the family of Libellulidae found 13 species, namely (Sympetrum vinicum, Macrodiplax cora, Neurothemis fluktuans, Neurothemis fulvia, Orthetrum sabina, Orthetrum testaceum, Pantala flavescens, Cratilla metallica, Pseudothemis zonata, Crocothemis servilia, Acisoma panorpoides, Tyriobapta torrida, dan Perithemis domitia). The diversity index (H') of dragonflies was obtained (1,146) which was categorized as moderate diversity index. The most common species found is Pantala flavescens and the least is Acisoma panorpoides.